Leprosy: Modern Views on the Modes of its Transmission - E. Yu. Yanchevskaya; O. A. Mesnyankina (Кубанский научный медицинский вестник)
The present article summarises existing ideas about the sources of leprosy and the modes of its transmission. The authors cover the evolution of views on the origin of this infection along with the mechanism underlying its transmission. Special attention is paid to modern research trends and current achievements in the sphere of modern leprology.